A cemented carbide-zirconia continuous gradient composite tool and a method for manufacturing the same

CN122938281APending Publication Date: 2026-10-20SU ZHOU ZHEN CAI KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611192695.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]目前,将硬质合金与氧化锆复合的技术主要有钎焊连接、涂层技术和双层突变烧结;钎焊连接采用银基焊料连接硬质合金基体与氧化锆刀头,界面为机械拼接结构,在断续切削热的力循环下,焊层抗剪强度不足,极易出现脱焊、崩刃,可靠性差;而涂层技术中的涂层厚度仅数微米,耐磨寿命有限,且涂层与基体热膨胀系数差异大,界面残余应力高,易起皮剥落;至于双层突变烧结,由于其采用两层材料分层压制后烧结,两相界面成分突跃,因烧结收缩率热导率差异显著,界面热应力集中,裂纹易沿界面扩展,整体断裂韧性低

Benefits of technology

[0024]本发明的硬质合金-氧化锆连续梯度复合刀具及其制备方法,通过在硬质合金芯层与氧化锆切削表层之间设置不少于五层的连续过渡梯度区,使WC-Co硬质合金质量分数由内向外由100%均匀线性递减至5%,3Y-TZP氧化锆质量分数由0%同步递增至95%,该梯度区使热膨胀系数、弹性模量等性能参数沿刀具厚度方向平滑过渡,从而将热应力分散于整个梯度区内,不产生应力尖峰,避免了界面裂纹产生,整体结构无界面和无拼接。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a cemented carbide-zirconia continuous gradient composite tool and its preparation method. The composite tool, from the inside to the outside along its thickness direction, consists of a cemented carbide core layer, a continuous transition gradient zone, and a zirconia cutting surface layer. The core layer is WC-Co cemented carbide, and the cutting surface layer is dominated by 3Y-TZP zirconia. In the gradient zone, the mass fraction of WC-Co cemented carbide continuously decreases from the core layer side to the surface layer side, while the mass fraction of 3Y-TZP zirconia increases simultaneously and continuously. The core layer and surface layer form a structure without a physical interface through the continuous transition gradient zone. The continuous transition gradient zone is prepared by stacking and co-pressing at least five layers of core layer powder and cutting surface powder with different proportions, followed by a single vacuum sintering. The composite tool prepared by this invention has high core layer bending strength and surface hardness, low friction effect, and no overall delamination or detachment risk. Its lifespan when machining aluminum parts and graphite materials is increased by more than 60% compared to conventional tools.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of superhard cutting tool materials technology, and particularly relates to a cemented carbide-zirconia continuous gradient composite tool and its preparation method. Background Technology

[0002] Carbide (WC-Co) is widely used in cutting tool substrates due to its high bending strength and excellent impact toughness. Meanwhile, 3Y-TZP tetragonal zirconia ceramic has non-magnetic properties, low coefficient of friction and high wear resistance, making it an ideal material for improving tool surface performance. Therefore, tools are currently being prepared by combining carbide and zirconia to meet actual performance requirements.

[0003] Currently, the main technologies for combining cemented carbide and zirconia include brazing, coating, and double-layer abrupt sintering. Brazing uses silver-based solder to connect the cemented carbide substrate and the zirconia cutting tip, resulting in a mechanically spliced ​​interface. Under the force cycle of intermittent cutting heat, the shear strength of the weld layer is insufficient, making it prone to detachment and chipping, leading to poor reliability. Coating technology uses coatings with a thickness of only a few micrometers, resulting in limited wear life. Furthermore, the difference in thermal expansion coefficients between the coating and the substrate leads to high residual stress at the interface, making it prone to peeling. As for double-layer abrupt sintering, due to the abrupt change in the composition of the two phases at the interface after pressing two layers of materials, the significant difference in sintering shrinkage and thermal conductivity causes thermal stress concentration at the interface, making cracks prone to propagate along the interface and resulting in low overall fracture toughness.

[0004] Therefore, the existing preparation methods cannot meet the actual use requirements and cannot meet the practical application needs. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art by providing a cemented carbide-zirconia continuous gradient composite cutting tool and its preparation method. The composite cutting tool prepared by this invention has the advantages of being interface-free and spliced, having high core toughness, and having a wear-resistant and non-magnetic surface.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is: a cemented carbide-zirconia continuous gradient composite tool, comprising: a core layer, a continuous transition gradient region, and a cutting surface layer distributed sequentially from the inside to the outside along the thickness direction of the composite tool;

[0007] The core layer is WC-Co cemented carbide; the cutting surface layer is mainly composed of 3Y-TZP zirconium oxide.

[0008] In the continuous transition gradient region, the mass fraction of WC-Co cemented carbide continuously decreases from the core layer side to the cutting surface layer side, while the mass fraction of 3Y-TZP zirconia continuously increases from the core layer side to the cutting surface layer side; the core layer and the cutting surface layer form a fully metallurgical bonded structure without physical interface through the transition gradient region.

[0009] Optionally, in the continuous transition gradient region, the mass fraction of WC-Co cemented carbide decreases uniformly and linearly from 100% to 5% from the core layer side to the cutting surface side, and the mass fraction of 3Y-TZP zirconia increases uniformly and linearly from 0% to 95% from the core layer side to the cutting surface side.

[0010] Optionally, in the core layer, the mass fraction of WC is 88-94%, the mass fraction of Co is 6-12%, and the particle size of WC powder is 0.6-1.2 μm; the cutting surface layer is sintered from 3 mol% Y2O3 stabilized tetragonal zirconia powder with a particle size of 0.3-0.8 μm.

[0011] Optionally, the continuous transition gradient region is formed by stacking and co-pressing no less than five layers of WC-Co cemented carbide powder and 3Y-TZP zirconia powder in different proportions, with the mass fraction difference between WC-Co cemented carbide powder and 3Y-TZP zirconia powder in adjacent layers being 15 to 25 wt%.

[0012] Optionally, each gradient layer in the continuous transition gradient region contains 0.2 to 0.5 wt% of nano-Co-coated zirconia composite powder, which accounts for 0.2 to 0.5 wt% of the total mass of the region.

[0013] Optionally, the clamping shank of the composite tool is entirely composed of the core layer, and the cutting edge area of ​​the tool falls entirely within the cutting surface layer.

[0014] Optionally, the composite tool is any one of a lathe insert, end mill, reamer, or slitting tool.

[0015] A method for preparing a cemented carbide-zirconia continuous gradient composite tool includes the following steps:

[0016] Step 1: Weigh WC-Co cemented carbide powder and 3Y-TZP zirconia powder according to the preset proportions of the core layer, continuous transition gradient zone and cutting surface layer, add molding agent to each and mix to obtain bulk powder of the core layer, bulk powder of the continuous transition gradient zone and bulk powder of the cutting surface layer.

[0017] Step 2: The core layer bulk powder, the continuous transition gradient zone bulk powder, and the cutting surface bulk powder obtained in Step 1 are sequentially filled into the mold in the order of decreasing WC-Co cemented carbide mass fraction from the inside to the outside and synchronously increasing 3Y-TZP zirconia mass fraction from the inside to the outside. After the mold is closed, pressure is applied for co-pressing and molding. After demolding, a compact is obtained.

[0018] Step 3: Place the pressed blank obtained in Step 2 in a protective atmosphere and heat it to degrease and remove the molding agent;

[0019] Step 4: Place the degreased compact in a vacuum sintering furnace, heat it to 1420-1460℃, and hold it at that temperature for liquid phase sintering;

[0020] Step 5: After sintering, cool to room temperature and perform post-processing on the sintered blank to obtain the composite tool.

[0021] Optionally, in step 1, each gradient layer powder in the continuous transition gradient region is further supplemented with nano-Co-coated zirconia composite powder accounting for 0.2 to 0.5 wt% of the total mass of the gradient layer.

[0022] Optionally, in step 4, the heating rate is 3℃ / min, and the holding time is 60-90min.

[0023] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0024] The present invention relates to a cemented carbide-zirconia continuous gradient composite tool and its preparation method. By setting no less than five continuous transition gradient zones between the cemented carbide core layer and the zirconia cutting surface layer, the mass fraction of WC-Co cemented carbide decreases uniformly and linearly from 100% to 5% from the inside out, while the mass fraction of 3Y-TZP zirconia increases simultaneously from 0% to 95%. This gradient zone allows performance parameters such as the coefficient of thermal expansion and elastic modulus to transition smoothly along the thickness direction of the tool, thereby dispersing thermal stress throughout the entire gradient zone, preventing stress peaks, avoiding interface cracks, and resulting in an overall structure without interfaces or splices.

[0025] The core layer of this invention uses WC-Co cemented carbide, whose bending strength meets the requirements of clamping torque and impact resistance in interrupted cutting. The cutting edge area is a 3Y-TZP zirconia enriched layer, which has a low coefficient of friction, anti-sticking properties, and non-magnetic characteristics, thus meeting the requirements of finishing. The two are seamlessly connected through a gradient zone, and 0.2-0.5wt% of nano-Co-coated zirconia composite powder is added to the gradient transition layer to improve the sintering compatibility of the two phases and eliminate interface cracks. This makes the composite tool have the integrated performance of high toughness of the core layer and high wear resistance and non-magnetic properties of the surface layer, and its service life is increased by more than 60% compared with conventional cemented carbide.

[0026] Furthermore, this invention employs a short-process route of layer-by-layer co-pressing molding followed by vacuum sintering, resulting in a short process cycle, high yield, and suitability for industrial mass production. Attached Figure Description

[0027] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:

[0028] Figure 1This is a cross-sectional view of a cemented carbide-zirconia continuous gradient composite tool according to an embodiment of the present invention;

[0029] Figure 2 This is a schematic diagram of the preparation method of a cemented carbide-zirconia continuous gradient composite tool in one embodiment of the present invention;

[0030] Among them: core layer 1, continuous transition gradient region 2, and cut surface layer 3. Detailed Implementation

[0031] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort should fall within the scope of protection of the present application.

[0032] For ease of understanding, the embodiments of this application are described in detail below. Please refer to [link / reference]. Figure 1 This embodiment provides a cemented carbide-zirconia continuous gradient composite tool, which includes, from the inside to the outside, a core layer 1, a continuous transition gradient region 2 and a cutting surface layer 3 along the thickness direction of the composite tool.

[0033] Specifically, the core layer 1 is a WC-Co cemented carbide, with a WC mass fraction of 88-94% and a Co mass fraction of 6-12%. The WC powder particle size is 0.6-1.2 μm. The core layer 1 uses a pure WC-Co cemented carbide formula to ensure the overall rigidity, bending strength, and torsional resistance of the composite tool, meeting the impact resistance requirements of machine tool clamping and intermittent cutting. The cutting surface layer 3 is mainly composed of 3Y-TZP zirconia, sintered from 3 mol% Y2O3-stabilized tetragonal zirconia powder with a powder particle size of 0.3-0.8 μm. It has the characteristics of being non-magnetic, low-friction, non-chip-accumulating, and highly wear-resistant, which can improve the finishing effect.

[0034] Furthermore, in the continuous transition gradient region 2, the mass fraction of WC-Co cemented carbide continuously decreases from the core layer 1 side to the cutting surface layer 3 side, while the mass fraction of 3Y-TZP zirconia increases synchronously and continuously. Preferably, the mass fraction of WC-Co cemented carbide decreases uniformly and linearly from 100% to 5%, and the mass fraction of 3Y-TZP zirconia increases uniformly and linearly from 0% to 95%, thus achieving a continuous and gradual change in composition, eliminating hard interfaces, and achieving seamless and interface-free operation.

[0035] The core layer 1 and the cutting surface layer 3 form a fully metallurgical bonded structure without physical interface through the continuous transition gradient region 2. The entire structure has no brazing layer, no coating layer, and no abrupt interface, which avoids the problems of cracking and peeling failure caused by interface defects in traditional composite tools.

[0036] Furthermore, each gradient layer in the continuous transition gradient region 2 contains 0.2 to 0.5 wt% of nano-Co-coated zirconia composite powder, which can be used to improve the sintering wettability between the cemented carbide phase and the zirconia phase and suppress the generation of interfacial microcracks.

[0037] Furthermore, the clamping shank of the composite tool is entirely composed of the core layer 1, and the cutting edge area of ​​the composite tool falls entirely within the cutting surface layer 3, thus allowing for excellent adaptation to practical applications. Simultaneously, the tool shape can be any of the following: turning insert, end mill, reamer, or slitting tool, to meet the application requirements of different scenarios.

[0038] See Figure 2 The present invention also discloses a method for preparing the above-mentioned composite cutting tool. The preparation method will be described in detail below through specific embodiments.

[0039] Example 1

[0040] This embodiment provides a five-layer gradient cemented carbide-zirconia continuous gradient composite slitting blade for continuous slitting of lithium battery separators. Its preparation method includes the following steps:

[0041] Step 1: Weigh the raw materials according to the proportions.

[0042] Core layer powder: The raw materials are weighed according to the ratio of 90wt% WC and 10wt% Co, with the WC powder having a particle size of 0.8μm and the Co powder having a particle size of 1.0μm.

[0043] Powder in the continuous transition gradient zone: WC-Co cemented carbide powder and 3Y-TZP zirconia powder were weighed according to the five-layer ratio shown in Table 1 below. Nano-Co coated zirconia composite powder accounting for 0.3wt% of the total mass of the layer was added to each gradient transition layer.

[0044]

[0045] Table 1

[0046] The surface powder used for cutting is 3 mol% Y2O3 stabilized tetragonal zirconia powder with a particle size of 0.6 μm.

[0047] The powders in the above proportions were respectively placed in a planetary ball mill with anhydrous ethanol and paraffin molding agent, mixed for 6 hours, and then vacuum dried and passed through an 80-mesh sieve to finally obtain core layer bulk powder, five-layer gradient transition layer powder and cutting surface bulk powder.

[0048] Step 2: The core layer bulk powder, the five-layer gradient transition layer bulk powder, and the cutting surface layer bulk powder obtained in Step 1 are sequentially filled into the rigid cemented carbide mold in the order of decreasing WC-Co cemented carbide mass fraction from the inside to the outside and synchronously increasing 3Y-TZP zirconia mass fraction from the inside to the outside. The mold is then closed and static pressure co-pressed for 45 seconds under a pressure of 22 MPa. After demolding, a compact with uniform density is obtained.

[0049] Step 3: Place the pressed preform obtained in Step 2 in a vacuum degreasing furnace, and under the protection of argon atmosphere, heat it to 400℃ at a rate of 0.8℃ / min, hold it at that temperature for 150min, and remove the paraffin molding agent.

[0050] Step 4: Transfer the degreased compact into a vacuum sintering furnace, evacuate to 1×10⁻²Pa, and heat to 1440℃ at a rate of 3℃ / min, hold for 75min for liquid phase sintering.

[0051] Step 5: After the heat preservation is completed, the temperature is controlled to be cooled to room temperature at a rate of 8℃ / min. High-purity argon gas is introduced during the cooling process. The sintered blank is ultrasonically cleaned and dried, and finally a slitting blade is obtained.

[0052] The performance test results of the slitting blade obtained in this embodiment are as follows: core layer bending strength: 2310 MPa, surface layer hardness: HV1360, surface layer residual compressive stress: 152 MPa.

[0053] In practical use, the five-layer gradient cemented carbide-zirconia continuous gradient composite slitting tool of the present invention was compared with conventional cemented carbide tools. Under the same cutting parameters, aluminum parts and graphite materials were machined respectively. The tool life of the present invention was more than 60% longer than that of conventional cemented carbide tools. This shows that the present invention extends the wear life of composite tools by eliminating interface stress concentration through continuous gradient transition, and by combining the high bending strength of the core layer with the high hardness of the surface layer.

[0054] Example 2

[0055] This embodiment provides a ten-layer gradient cemented carbide-zirconia continuous gradient crown drill and end mill. The difference between its preparation method and that of Embodiment 1 is that the continuous transition gradient region powder is set as a ten-layer gradient transition region. WC-Co cemented carbide powder and 3Y-TZP zirconia powder are weighed according to the ten-layer ratio shown in Table 2 below. Nano-Co coated zirconia composite powder accounting for 0.3wt% of the total mass of the layer is added to each gradient transition layer.

[0056]

[0057] Table 2

[0058] The core bending strength of the drill and milling cutter obtained in this embodiment is ≥2300MPa, the surface hardness is HV1350~HV1380, and the surface residual compressive stress is 130~160MPa.

[0059] Under the same cutting parameters, graphite and glass fiber composite materials were machined using both the drill-and-mill cutter of this embodiment and the brazed zirconia drill-and-mill cutter. The results showed that the drill-and-mill cutter of this embodiment did not exhibit tooth breakage or tipping during continuous cutting, and the tool integrity remained good. In contrast, the brazed control tool showed weld layer cracking and chipping failure within a short time under the same cutting conditions. Therefore, this invention, through its interface-free and splice-free structure, eliminates the risk of weld detachment and chipping at the brazed interface under impact loads, making it suitable for long-term precision machining of graphite and glass.

[0060] The above-described embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A cemented carbide-zirconia continuous gradient composite tool, characterized in that, include: The core layer, the continuous transition gradient zone, and the cutting surface layer are distributed sequentially from the inside to the outside along the thickness direction of the composite tool. The core layer is WC-Co cemented carbide; the cutting surface layer is mainly composed of 3Y-TZP zirconium oxide. In the continuous transition gradient region, the mass fraction of WC-Co cemented carbide continuously decreases from the core layer side to the cutting surface layer side, while the mass fraction of 3Y-TZP zirconia continuously increases from the core layer side to the cutting surface layer side; the core layer and the cutting surface layer form a fully metallurgical bonded structure without physical interface through the transition gradient region.

2. The cemented carbide-zirconia continuous gradient composite tool as described in claim 1, characterized in that: In the continuous transition gradient region, the mass fraction of WC-Co cemented carbide decreases uniformly and linearly from 100% to 5% from the core layer side to the cutting surface side, while the mass fraction of 3Y-TZP zirconia increases uniformly and linearly from 0% to 95% from the core layer side to the cutting surface side.

3. The cemented carbide-zirconia continuous gradient composite tool as described in claim 1, characterized in that: In the core layer, the mass fraction of WC is 88-94%, the mass fraction of Co is 6-12%, and the particle size of WC powder is 0.6-1.2 μm; the cutting surface layer is sintered from 3 mol% Y2O3 stabilized tetragonal zirconia powder with a particle size of 0.3-0.8 μm.

4. The cemented carbide-zirconia continuous gradient composite tool as described in claim 1, characterized in that: The continuous transition gradient region is formed by stacking and co-pressing no less than five layers of WC-Co cemented carbide powder and 3Y-TZP zirconia powder in different proportions, with the mass fraction difference between WC-Co cemented carbide powder and 3Y-TZP zirconia powder in adjacent layers being 15 to 25 wt%.

5. The cemented carbide-zirconia continuous gradient composite tool as described in claim 1, characterized in that: Each gradient layer in the continuous transition gradient region contains 0.2–0.5 wt% of nano-Co-coated zirconia composite powder, which accounts for 0.2–0.5 wt% of the total mass of the region.

6. The cemented carbide-zirconia continuous gradient composite tool as described in claim 1, characterized in that: The clamping shank of the composite tool is entirely composed of the core layer, and the cutting edge area of ​​the composite tool falls entirely within the cutting surface layer.

7. The cemented carbide-zirconia continuous gradient composite tool as described in claim 1, characterized in that: The composite tool is any one of a lathe insert, end mill, reamer, or slitting tool.

8. A method for preparing a cemented carbide-zirconia continuous gradient composite tool as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1: Weigh WC-Co cemented carbide powder and 3Y-TZP zirconia powder according to the preset proportions of the core layer, continuous transition gradient zone and cutting surface layer, add molding agent to each and mix to obtain bulk powder of the core layer, bulk powder of the continuous transition gradient zone and bulk powder of the cutting surface layer. Step 2: The core layer bulk powder, the continuous transition gradient zone bulk powder, and the cutting surface bulk powder obtained in Step 1 are sequentially filled into the mold in the order of decreasing WC-Co cemented carbide mass fraction from the inside to the outside and synchronously increasing 3Y-TZP zirconia mass fraction from the inside to the outside. After the mold is closed, pressure is applied for co-pressing and molding. After demolding, a compact is obtained. Step 3: Place the pressed blank obtained in Step 2 in a protective atmosphere and heat it to degrease and remove the molding agent; Step 4: Place the degreased compact in a vacuum sintering furnace, heat it to 1420-1460℃, and hold it at that temperature for liquid phase sintering; Step 5: After sintering, cool to room temperature and perform post-processing on the sintered blank to obtain the composite tool.

9. The method for preparing the cemented carbide-zirconia continuous gradient composite tool as described in claim 8, characterized in that: In step 1, each gradient layer powder in the continuous transition gradient region is further supplemented with nano-Co-coated zirconia composite powder, accounting for 0.2 to 0.5 wt% of the total mass of the gradient layer.

10. The method for preparing the cemented carbide-zirconia continuous gradient composite tool as described in claim 8, characterized in that: In step 4, the heating rate is 3℃ / min, and the holding time is 60-90min.